Endoscopic ultrasound-guided radiofrequency ablation of pancreatic microcystic serous cystic neoplasms: a retrospective study - Oh, Dongwook; Ko, Sung Woo; Seo, Dong-Wan; Hong, Seung-Mo; Kim, Jin Hee; Song, Tae Jun; Park, Do Hyun; Lee, Sung Koo; Kim, Myung-Hwan (Endoscopy, 2020)
Background Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) has been increasingly used for the management of various solid pancreatic tumors. This study aimed to evaluate the feasibility and safety of EUS-RFA for serous cystic neoplasms (SCNs).Methods 13 patients with microcystic SCNs with honeycomb appearance underwent EUS-RFA using a 19-gauge RFA needle. Before ablation, cystic fluid was aspirated until a thin layer of fluid remained.Results EUS-RFA was successful in all patients. Seven patients underwent a single session and the remaining six patients underwent a second session of EUS-RFA. One patient (7.7 %) experienced self-limited abdominal pain after EUS-RFA. During a median follow-up period of 9.21 months (interquartile range [IQR] 5.93 – 15.38), the median volume of the SCNs decreased from 37.82 mL (IQR 15.03 – 59.53) at baseline to 10.95 mL (IQR 4.79 – 32.39) at the end of follow-up. A radiologic partial response was achieved in eight patients (61.5 %).Conclusions EUS-RFA is technically feasible and showed an acceptable rate of adverse events for patients with SCNs. A long-term follow-up study is required to evaluate the efficacy of EUS-RFA.